Tundra Mouse : A Storyknife Tale - McDonald, Megan (New York : Orchard Books, 1997)
Using a traditional technique called storyknifing, two Yupik Eskimo sisters share a story about the mice that made a nest out of tinsel from the Christmas tree.
"A Richard Jackson book."
Keywords: Yupik Eskimos -- Juvenile fiction; Eskimos -- Juvenile fiction; Mice -- Juvenile fiction; Storytelling -- Juvenile fiction